Pengembangan Aset dan Potensi Santri Melalui Pelatihan Pembuatan Peralatan Sekolah dari Barang Bekas di Pondok Pesantren Putri Miftahul Mubtadiin Ar-Ridlo Krempyang Tanjunganom Nganjuk - ahmad saifudin; Muhammad Imam Khosyiin (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
The existence of pesantren is expected to be able to transform and become an institution that not only focuses on teaching sciences and the yellow book, but also teaches science, technology, and informatics sciences that still maintain Islamic values ​​both in the process and content of knowledge so that later they can gave birth to the kyai as well as the sanities. These activities are generally in the form of field work practices or real work lectures, where the location, theme, method and length of time for implementation are determined by the respective universities. In order to explore the potential and develop Islamic boarding school assets during the COVID-9 pandemic Researchers try to be flexible to find loopholes so that social and cultural activities in the pesantren continue to run conducive Miftahul mubtadiin Ar ridlo Islamic boarding school. Optimizing products from farming activities at Islamic boarding schools can take energy from the students in turn and also take energy from the community to be employed. The harvest can be sold to finance operational activities at the pesantren.